Effect of Yd:YAG laser irradiation on the shear bond strength of orthodontic metal brackets - Moreira,Fernando César (2020)
ABSTRACT Objective: The purpose of this study was to evaluate the effect of the Yd:YAG laser irradiation on orthodontic bracket base surface. Shear bond strength (SBS) values and sites of the bonding failure interfaces were quantified. Methods: Brackets were divided into two groups: OP (One Piece - integral sandblast base) and OPL (One Piece - laser irradiation). The brackets were randomly bonded on an intact enamel surface of 40 bovine incisors. The SBS tests were carry out using a universal test machine. A stereomicroscopy was used to evaluate the adhesive remnant index (ARI), and surface characterization was performed by scanning electron microscopy (SEM). Student’s t-test was used to compare the SBS between the two groups (p< 0.05). Frequencies and chi-square analysis were applied to evaluate the ARI scores. Results: OPL group showed higher value (p< 0.001) of SBS than OP group (43.95 MPa and 34.81 MPa, respectively). ARI showed significant difference (p< 0.001) between OPL group (ARI 0 = 100%) and OP group (ARI 0 = 15%). SEM showed a higher affinity between the adhesive and the irradiated laser base surface. Conclusions: Yd:YAG laser irradiation on bracket base increased SBS values, showing that bonding failure occurs at the enamel/adhesive interface. Laser-etched bracket base may be used instead of conventional bases in cases where higher adhesion is required, reducing bracket-bonding failure.